Suspected Lonely Mouse Syndrome as a Cage Effect in a Drug Safety Study. (9th May 2018) - Ye, Xiaobu; Itzoe, MariaLisa; Sarabia-Estrada, Rachel; DeTolla, Louis; Tyler, Betty M.; Guarnieri, Michael
Abstract : Studies have demonstrated that buprenorphine, a front line drug for veterinary analgesia, may alleviate symptoms of chronic pain. A cage side observation protocol was used to record behavioral signs in a mouse clinical trial of extended release buprenorphine. A retrospective review of the observations for signs of pain and stress revealed that mice given a fivefold overdose of buprenorphine (16.25 mg/kg) showed lethargy and facial signs associated with stress. However, similar signs were observed in the drug-free control mice as early as Day 3 of single-cage housing. This appears to be the first report of cage effects in a clinical trial for a veterinary drug.